The use of social media business tools by SMEs in Gauteng, South Africa - Maphathe, Tlalane Leah (My University, 2019)
Social media platforms have business tools that businesses can use to maximise their interaction with new and potential customers. In addition, these business tools to make it easier to market products and services exponentially if adopted well. Therefore, social media marketing has become extremely important for any business trying to grow and adapt to the digital world. Through social media business tools, brands are able to trace what is working for their business as well as co-create products with customers in order to best serve them. This emphasises Mark Granovetter’s philosophy on the strength of weak ties. Currently most SMEs in South Africa fail within two to three years of operating. Some of the reasons to this failure rate include lack of access to market, lack of funding as well as poor marketing of the business. Using social media business tools allows companies to access great numbers of people that are active on social media platforms world-wide. This makes social media a conducive place for businesses to use in order to access those active, existing and new customers. Customers are every company’s most imperative asset and acquiring more customers improves the performance of a company, which in turn contributes to the growth of the SME. Therefore, SMEs need to understand how to use social media business tools effectively in order to be able to increase their customer acquisition. The purpose of this research is to evaluate the use of social media business tools on SME performance specifically focusing on increased customer acquisition. The study adopted a quantitative and positivist manner. A survey was distributed through an online survey link, emails as well as physical hand-outs. The study showed a positive perspective of SMEs in terms of using social media business tools to increase their customer-base. The findings of this paper contribute to the knowledge of SME growth and social media.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management in Entrepreneurship and New Venture Creation, February 2019
Keywords: Social media; Social media--Economic aspects; Business communication